BIO-ENGINEERING FOR POLLUTION PREVENTION THROUGH DEVELOPMENT OFBIOENERGY MANAGEMENT - Omer, Abdeen Mustafa (JOURNAL OF ADVANCES IN BIOLOGY, 2013)
This Article discusses a comprehensive review of biomass energy sources, environment and sustainable development. This includes all the biomass energy technologies, energy efficiency systems, energy conservation scenarios, energy savings and other mitigation measures necessary to reduce emissions. The current literature is reviewed regarding the ecological, social, cultural and economic impacts of biomass technology. This article gives an overview of present and future use of biomass as an industrial feedstock for production of fuels, chemicals and other materials. However, to be truly competitive in an open market situation, higher value products are required. Results suggest that biomass technology must be encouraged, promoted, invested, implemented, and demonstrated, but especially in remote rural areas.